OPTIMUS: Software for Efficient Manipulation and Control of Industrial Robots - Tovar Tovar, Michael; Rivera Gómez, Andrés Eduardo; Hile Bustos, Pedro Daniel; Rodríguez Serrezuela, Ruthber (I+ T+ C- Research, Technology and Science, 2023)
The article introduces an offline interaction software that exhibits the MR5 robot developed by the Corporación Universitaria del Huila - CORHUILA in its interface. This robot is an anthropomorphic system with 5 degrees of freedom. The primary purpose of this software is to enable interaction with the robot without needing its physical presence. This is achieved by planning different trajectories for the robot and obtaining a simulation of its physical behavior. After exporting and importing the data to the real-time control software called "Mach3", this simulation is performed. During this interaction, the previously planned movements of the robot are observed. The software interface presents a detailed tracking of the behavior of each of the robot's joint positions, including information about its velocity and acceleration. The kinematic and dynamic model and its analysis are obtained with due mathematical rigor.